Hypolipidemic Effects of Modified Edamame Tempeh Flour on Lipid Profile Levels in Dyslipidemia Rats - Dika Nurkistin; Didik Gunawan Tamtomo; Budiyanti Wiboworini (Universitas Airlangga, 2022)
Background: Dyslipidemia is a lipid metabolism disorder that causes an increase or decrease in plasma lipid concentrations. Comprehensive management is an attempt to prevent and reduce dyslipidemia, one of which is nutritional therapy. Edamame contains nutrients such as protein, fat, fiber, and isoflavones that have the potential to improve lipid profiles. Edamame tempeh production is one way to improve product quality that is improving nutritional quality, digestibility, and bioavailability. Edamame tempeh modification is conducted by adding yeast Saccharomyces cerevisiae. This yeast plays a role in increasing the isoflavone levels and the product containing β-glucan. Objectives: This research aims to analyze the effects of edamame tempeh flour (ET) and modified edamame tempeh flour (MET) on lipid profile levels in dyslipidemic rats. Methods: This research was a true experimental with a randomized controlled group pretest-posttest design. Thirty-six Sprague Dawley male white rats that met the inclusion criteria were randomized and divided into six treatment groups consisting of negative control, positive control, the dose of ET flour was 2.7 g/200gBW and 5.4 g/200gBW, the dose of MET flour was 2.7 g/200gBW and 5.4 g/200gBW. The intervention was carried out once per day in the morning for 28 days. The parameters observed included total cholesterol, LDL-C, and HDL-C levels measured by the CHOP-PAP method and triglyceride levels using the GPO-PAP method with a spectrophotometer measuring instrument. Examination of lipid profile levels was carried out three times. All statistical tests used a 95% significance level. Results: There was a significant difference in the decrease in total cholesterol, LDL-C, and triglyceride levels as well as an increase in HDL-C levels compared to before the intervention (p<0.05). Conclusions: The administration of ET flour and MET flour could significantly reduce total cholesterol, LDL-C, triglyceride, and increased HDL-C, but the administration of MET flour, especially at a dose of 5.4 g/200gBW, showed a more effective improvement in lipid profile and approached the positive control group compared to ET flour.